2010
DOI: 10.1186/1475-2840-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol compared to carvedilol deteriorates insulin-stimulated endothelial function in patients with type 2 diabetes - a randomized study

Abstract: AimStudies of beta blockade in patients with type 2 diabetes have shown inferiority of metoprolol treatment compared to carvedilol on indices of insulin resistance. The aim of this study was to examine the effect of metoprolol versus carvedilol on endothelial function and insulin-stimulated endothelial function in patients with type 2 diabetes.Method24 patients with type 2 diabetes were randomized to receive either 200 mg metoprolol succinate or 50 mg carvedilol daily. Endothelium-dependent vasodilation was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
2
16
1
1
Order By: Relevance
“…These data coincide with Fonarow et al [55]; Fonseca [47]; Deedwania [56]; Gastone and Colin [57]. Carvedilol reduces peripheral vascular resistance, have little or no effect on cardiac output, and improve endothelial function through anti-oxidative and free radical scavenger properties [56].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These data coincide with Fonarow et al [55]; Fonseca [47]; Deedwania [56]; Gastone and Colin [57]. Carvedilol reduces peripheral vascular resistance, have little or no effect on cardiac output, and improve endothelial function through anti-oxidative and free radical scavenger properties [56].…”
Section: Discussionsupporting
confidence: 74%
“…Our data in the present study revealed a significant decrease in blood glucose level, serum insulin and a significant improvement in insulin sensitivity in carvedilol treated group in comparison to UHFD group. These data are in accordance with Wilson et al [44]; Stefania et al [45]; Kveiborg et al [46]; Fonseca, [47]. In contrast to our results Bakriset al [48] found that carvedilol did not affect glycemic control but improves some components of the metabolic syndrome relative to metoprolol in patients with DM and hypertension.…”
Section: Discussioncontrasting
confidence: 57%
“…Zhoa et al described vascular benefits of carvedilol through preservation of endothelial junctions, independent of β‐AR inhibition (Zhao, Yang, You, Cui, & Gao, 2007). Furthermore, specific comparison of metoprolol and carvedilol in patients with type 2 diabetes showed a detrimental effect of metoprolol on insulin‐stimulated endothelial function (Kveiborg et al, 2010). As vasodilation, particularly in skeletal muscle, is crucial to glucose disposal (Keske et al, 2017), carvedilol's ability to maintain or improve vascular function may lead to better glycemic control in patients with diabetes than other inhibitors selective for β1‐AR (Haas et al, 2003; Jacob & Henriksen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the addition of carvedilol for BP control resulted in a significant decrease in triglyceride, total cholesterol, and non-high-density lipoprotein (HDL) cholesterol levels, whereas the use of metoprolol resulted in a significantly greater rate of initiation of statin therapy or an increase in the dose of existing statin therapy [33]. Finally, insulin-stimulated endothelial function was preserved during treatment with carvedilol whereas it was blunted during treatment with metoprolol [34]. However, although a favorable metabolic profile might be considered in selecting a specific β-blocker, these agents, both traditional and newer, have wellestablished indications in diabetes patients with a previous myocardial infarction, rhythm disorders, or heart failure because of their proven effectiveness in reducing mortality [28].…”
Section: Metabolic Effects Of Antihypertensive Drugs: What We Alreadymentioning
confidence: 94%